The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1590/s1807-59322009000400011
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial and Non-Endothelial Coronary Blood Flow Reserve and Left Ventricular Dysfunction in Systemic Hypertension

Abstract: Rocha AM, Salemi VMC, Neto PAL, Matsumoto AY, Pereira VFA, Fernandes F, Nastari L, Mady C. Endothelial and non-endothelial coronary blood flow reserve and left ventricular dysfunction in systemic hypertension. Clinics. 2009;64(4):327-35 OBJECTIVES: We evaluated the impairment of endothelium-dependent and endothelium-independent coronary blood flow reserve after administration of intracoronary acetylcholine and adenosine, and its association with hypertensive cardiac disease. INTRODUCTION: Coronary blood fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…At the same time, cardiac function was significantly suppressed during 2.5% isoflurane inhalation compared with during 1% isoflurane inhalation or adenosine infusion in those mice, especially in the AR mice. We also found that CFR was closely related to cardiac function, which was in accord with previous studies in humans (20) and mice (10). All of the evidence suggests that high-concentration isoflurane-induced cardiac dysfunction may lead to underestimation of CFR.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…At the same time, cardiac function was significantly suppressed during 2.5% isoflurane inhalation compared with during 1% isoflurane inhalation or adenosine infusion in those mice, especially in the AR mice. We also found that CFR was closely related to cardiac function, which was in accord with previous studies in humans (20) and mice (10). All of the evidence suggests that high-concentration isoflurane-induced cardiac dysfunction may lead to underestimation of CFR.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, CFR is closely related with cardiac function (10,20). Given that isoflurane can depress cardiac function through myofilament desensitization (5), the findings in mice without significant cardiac overloading could not be simply extrapolated to mice with loading changes (e.g., pressure or volume overload) or cardiac remodeling (concentric or eccentric hypertrophy).…”
mentioning
confidence: 99%
“…Hemodynamic overload promotes myocyte stretch, the release of intracellular calcium, the activation of calcineurin and the induction of gene expression reprogramming 1. In athletes, left ventricular hypertrophy (LVH) is regarded as a physiological response that results from a hemodynamic overload; this physiological response does not result in the harmful effects of hypertension development or other heart diseases 1012. The literature explains physiological LVH as the result of a volume and pressure overload that results from intense physical training (the hemodynamic stimulus), which is not necessarily accompanied by neural and humoral changes 13…”
Section: Introductionmentioning
confidence: 99%
“…1 Endothelial dysfunction is an important, early and reversible feature of atherogenesis. 6 Noninvasive transthoracic ultrasound imaging of coronary blood flow is increasingly being used to identify derangements of coronary microcirculation at the level of coronary flow in the absence of epicardial coronary stenosis. 4,5 Impairment of endothelium-dependent coronary vasodilatation capacity is one of the mechanisms responsible for inadequate myocardial flow early in hypertensive patients before the development of morphological alterations.…”
mentioning
confidence: 99%